Terminal blood lactate concentrations for distance runners for races from 400 m to 10 km - Buffington, S. M.; Sucec, A. A.; Burks, J.; Trone, D. (Medicine & Science in Sports & Exercise, 2000)
Runners (M = 12; F = 12) performed all-out runs over distances of 400 m, 800 m, 1500 m, 3 km, 5 km, and 10 km on a 400 m track. Lactate values immediately upon finishing were determined. The average lactate values for the distances were 6.88, 8.32, 9.99, 10.5, 9.91, and 8.14 mmol/l. Implication. Lactate values are poor indicators of work intensity. The duration of the performance has to be considered to evaluate whether the full involvement in anaerobic glycolysis is possible or whether high levels of blood lactate can be sustained.